Experimentally investigate influence of 3d printing parameters on rigidity of PLA parts - Abdelghani ELJIHAD; Mohammed NASSRAOUI; Othmane BOUKSOUR (Incertitudes et Fiabilité des Systèmes Multiphysiques)
The aim of this paper is to analyze the impact of 3D printing parameters on the strength of polylactic acid (PLA) parts. We will look at how the mechanical characteristics of printed objects are influenced by material properties, extruder temperature, printing speed and layer thickness. We will emphasize the importance of monitoring print parameters to ensure optimal quality and reproducibility of parts using traction tests on samples. To develop empirical models that will establish a correlation between print parameters and mechanical properties, we will use the Taguchi method. Our goal is to find the optimal parameters, such as layer thickness, extrusion temperature and print speed, in order to maximum rigidity of 3D printed parts.